2017
DOI: 10.7753/ijsea0605.1001
|View full text |Cite
|
Sign up to set email alerts
|

An Optimal Design of the Inlet and Outlet Obstacles at USBR II ‎Stilling Basin

Abstract: Hydraulic jump is one of the rapidly varied flows that different elements can be employed to control it in stilling basins. The purpose of this study is optimal design of obstacles at USBR II stilling basin of Nazloochay dam model. For this purpose, the obstacles at the end chute with thicknesses and heights of 0.5, 1, 1.5 and 2 m and 2, 3 and 4 steps at the end USBR II stilling basin have been considered. Then for the most optimal state, the pressure, water surface profile, turbulent kinetic energy, and turbu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…However, as compared with lower tailwater levels, the values for TKEs in 129.40 m tailwater were found to be lower and the TKEs levelled off earlier within and after the HJ. In the HJ regions, following the similar trends for the 129.10 and 129.40 m tailwater levels, the TKEs in the 129.70, 129.99, and 130.30 m tailwater levels reached 3.20, 3.15, and 2.90 m 2/ s 2 , respectively, and their values decreased after the HJ, as illustrated in Figure 15c-e. Additionally, the results for the TKEs showed a trend that was noted in the numerical studies (Nikmehr and Aminpour [71]; Soori et al [76]). Figure 16 shows 2D illustrations of turbulent kinetic energies captured using RNG-K-ε at five different tailwater levels.…”
Section: Turbulent Kinetic Energies (Tkes)supporting
confidence: 73%
See 2 more Smart Citations
“…However, as compared with lower tailwater levels, the values for TKEs in 129.40 m tailwater were found to be lower and the TKEs levelled off earlier within and after the HJ. In the HJ regions, following the similar trends for the 129.10 and 129.40 m tailwater levels, the TKEs in the 129.70, 129.99, and 130.30 m tailwater levels reached 3.20, 3.15, and 2.90 m 2/ s 2 , respectively, and their values decreased after the HJ, as illustrated in Figure 15c-e. Additionally, the results for the TKEs showed a trend that was noted in the numerical studies (Nikmehr and Aminpour [71]; Soori et al [76]). Figure 16 shows 2D illustrations of turbulent kinetic energies captured using RNG-K-ε at five different tailwater levels.…”
Section: Turbulent Kinetic Energies (Tkes)supporting
confidence: 73%
“…The literature only revealed one study that employed a one-dimensional (1D) HEC-RAS model to investigate the limited hydraulic parameters downstream of the studied barrage [36]. Therefore, the present FLOW-3D model results are compared with 1D and the relevant studies from the literature, i.e., Bayon-Barrachina and Lope-Jimenez [4], Chaudhry [36], Ead and Rajaratnam [11][12][13], Nikmehr and Aminpour [71], Soori et al [76], and Kucukali and Chanson [94]. After comparing with the results of the free surface profiles of HJs at the studied tailwater levels, it is revealed that the previously used 1D model underestimates the locations of the HJs; for which the errors reached 8%.…”
Section: Discussion and Real-world Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors found that the original design dimensions of the chute blocks led to the optimal performance of the basin, since they achieved better submergences and higher dissipation efficiency. Soori et al (2017) also tested different sizes for the chute blocks in a USBR Type-II stilling basin, changing the end sill for a series of steps too. The results presented by these authors also point out to an optimal dimension of the chute blocks in line with the original design.…”
Section: Stilling Basin Modified Designmentioning
confidence: 99%